E-commerce, Financial Technology, Media Sosial dan Pengaruhnya terhadap Pendapatan UMKM Kota Tasikmalaya - Desiana, Desiana; Bintari, Vivi Indah; Nanda, Ulfa Luthfia (Owner : Riset dan Jurnal Akuntansi, 2024)
MSMEs are the pillars of the national economy, MSMEs are also economic drivers as well as absorbing quite a lot of labor, however the pandemic attack had quite a bad impact on MSMEs, MSMEs need to work hard to be able to recover from the downturn of the pandemic, and now MSMEs can start developing their businesses again by take advantage of many opportunities, especially in business digitalization. This research shows the influence of e-commerce, financial technology, and social media on MSME income in Tasikmalaya city. The population in this study is 123.010 MSMEs in Tasikmalaya City, from this population, 100 samples were obtained used probability sampling with simple random sampling technique. The data analysis technique in this research used multiple linier regression analysis. The results of this research show that the e-commerce partially influences the income of MSMEs in Tasikmalaya City, while the financial technology and social media partially have no influence on MSME income in Tasikmalaya city, and simultaneously e-commerce, financial technology and social media influence MSME income in Tasikmalaya City.